دور القيادة الرقمية المستدامة في تعزيز الأداء المستدام للمؤسسات التعليمية: رؤية مستقبلية / دراسة تطبيقية في جامعة وارث الانبياء وجامعة الطف وجامعة الصفوة (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Objective of the study: Educational institutions live in an era characterized by accelerating technological transformations, as the increasing impact of digital technology appears on all aspects of daily life. In this context, educational institutions ask how sustainable digital leadership can contribute to achieving sustainable performance and enhancing educational excellence. This study is an applied analysis of the role of sustainable digital leadership in improving the sustainable performance of educational institutions (Warith Al-Anbiya University, Al-Taf University, and Al-Safwa University). The study aims to analyze the role of sustainable digital leadership in enhancing the sustainable performance of educational institutions, and to provide a future vision of the impact of this leadership on digital transformation in educational institutions.The importance of the study: Highlighting the importance of digital transformation and sustainable leadership in enhancing educational performance, and providing guidance for educational institutions to improve the sustainability of their performance in the field of digital education.Study methodology: The study is based on a survey approach, where a questionnaire was distributed to faculty members at universities (Warith al-Anbiya University, Al-Taf University, and Al-Safwa University), and 122 professors were selected from various colleges to collect the data necessary for analysis.Study conclusions: The results show that sustainable digital leadership plays a vital role in enhancing the sustainable performance of educational institutions, and it also shows the impact of digital transformation in improving the efficiency of the educational process and increasing communication.Study recommendations: Enhancing the training of leaders to use technology sustainably and effectively, encouraging institutions to develop digital strategies that enhance communication and stimulate e-learning, and promoting the sustainable exchange of experiences among faculty members to stimulate innovation and continuous improvement.